Long‐term efficacy and safety of ertugliflozin monotherapy in patients with inadequately controlled T2DM despite diet and exercise: VERTIS MONO extension study. Issue 6 (23rd February 2018) - Aronson, Ronnie; Frias, Juan; Goldman, Allison; Darekar, Amanda; Lauring, Brett; Terra, Steven G.
Abstract : Aim: This phase III, multicentre, randomized study (ClinicalTrials.gov ; NCT01958671) evaluated the efficacy and safety of ertugliflozin monotherapy in adults with inadequately controlled type 2 diabetes (glycated haemoglobin [HbA1c], 7.0% to 10.5% [53‐91 mmol/mol]) despite diet and exercise. Materials and methods: The 52‐week study comprised a 26‐week, double‐blind, placebo‐controlled period (Phase A) during which 461 participants received placebo, ertugliflozin 5 mg/d or ertugliflozin 15 mg/d. This was followed by a 26‐week active‐controlled period (Phase B) during which participants in the placebo group who had not received glycaemic rescue therapy had blinded metformin added. Results to Week 52 are reported. Because of the use of metformin in Phase B, no statistical comparisons of efficacy were made between the ertugliflozin and placebo/metformin groups at Week 52. Results: The mean (standard error) change from baseline to Week 52 in HbA1c was −0.9% (0.1) and −1.0% (0.1) in the ertugliflozin 5 and 15 mg groups, respectively. The proportions of participants with HbA1c <7.0% at Week 52 were 25.6% and 28.5%, respectively. Ertugliflozin reduced fasting plasma glucose, body weight and systolic blood pressure (SBP). The incidence of genital mycotic infections (GMIs) in females was significantly higher in both ertugliflozin groups (5 mg, 26.9%; 15 mg, 29.0%) vs the placebo/metformin group (9.9%), and in males was significantly higher in the 15 mg group (7.8%) vs the placebo/metformin group (1.2%). Ertugliflozin was not associated with increased incidence of urinary tract infections, symptomatic hypoglycaemia or hypovolaemia adverse events compared with placebo/metformin. Conclusions: Ertugliflozin treatment over 52 weeks improved glycaemic control and reduced body weight and SBP, but increased GMIs.